Formation of self-organized organic-inorganic hybrids - Gorbach, T.; Kostylyov, V.; Melakh, V.; Roshchina, N.; Smertenko, P.; Wisz, G. (Вісник Українського матеріалознавчого товариства, 2015)
The morphology features and peculiarities of current-voltage characteristics of selforganized organic–silicon hybrids were investigated. The organic layers were formed by chemical bath deposition at room temperatures of phosphorus doped n-type FZ Si-patterned substrate. The pattern was formed by etching in anisotropic etch on the base of aqueous solution of potassium hydrate KOH and isopropyl alcohol. The following aqueous solutions of organic heterocyclic aromatic compounds were used for hybrids formation: sulfacyl sodium, procainamide hydrochloride (novocain) and lamotridgine. These hybrids have shown different types of morphology. This depends on substrate properties, time deposition and organic concentration in water solution. The photovoltaic effect of organic-pattern silicon is the result of chemisorptions of functional amine, amide, carboxyl, thiols and halogen groups on silicon pattern-type surface. At the same time these results have proven that the substrate of start and classic morphology in pyramid form is favored for formation of organic-silicon hybrids for photovoltaic application.